2024
DOI: 10.1108/tlo-01-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Management learning in public healthcare during pandemics

Ritva Rosenbäck,
Ann Svensson

Abstract: Purpose This study aims to explore the management learning during a long-term crisis like a pandemic. The paper addresses both what health-care managers have learnt during the COVID-19 pandemic and how the management learning is characterized. Design/methodology/approach The paper is based on a qualitative case study carried out during the COVID-19 pandemic at two different public hospitals in Sweden. The study, conducted with semi-structured interviews, applies a combination of within-case analysis and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The sixth article is written by Ritva Rosenbäck and Ann Svensson (Rosenbäck & Svensson, 2024) and contributes to an understanding on how management learning is supported during a long-term crisis like a pandemic, characterizing what health-care managers have learnt, and how the management learning is characterized, during the COVID-19 pandemic. In the study, the authors have carried out a qualitative case study pandemic at two different public hospitals in Sweden, including a combination of a deductive within-case analysis and a cross-case analysis.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…The sixth article is written by Ritva Rosenbäck and Ann Svensson (Rosenbäck & Svensson, 2024) and contributes to an understanding on how management learning is supported during a long-term crisis like a pandemic, characterizing what health-care managers have learnt, and how the management learning is characterized, during the COVID-19 pandemic. In the study, the authors have carried out a qualitative case study pandemic at two different public hospitals in Sweden, including a combination of a deductive within-case analysis and a cross-case analysis.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…By studying and comparing the practice of two hospitals in Sweden, Rosenbäck & Svensson (2024) found that it was difficult for managers to grasp the new situation during the declared pandemic. They gathered information from their international colleagues and their own hospitals to assess capacity needs and select treatment methods.…”
Section: Management Learning In Crisis Situationmentioning
confidence: 99%
“…For this reason, distributed management was required, incorporating the perspectives of different stakeholders. In such cases, Rosenbäck & Svensson (2024) suggest the use of a framework that proposes five management tasks during a crisis situation: sense-making, decision-making, meaning-making, crisis management and learning. However, after the crisis has ended, further sense-making and learning are needed to determine what has been learned and what benefits it has for future work, so that some work practices are permanently changed.…”
Section: Management Learning In Crisis Situationmentioning
confidence: 99%